2013
DOI: 10.1631/jzus.b1300102
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants

Abstract: Abstract:The study on biochar derived from plant biomass for environmental applications is attracting more and more attention. Twelve sets of biochar were obtained by treating four phytoremediation plants, Salix rosthornii Seemen, Thalia dealbata, Vetiveria zizanioides, and Phragmites sp., sequentially through pyrolysis at 500 °C in a N 2 environment, and under different temperatures (500, 600, and 700 °C) in a CO 2 environment. The cation exchange capacity and specific surface area of biochar varied with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(75 citation statements)
references
References 37 publications
8
60
0
3
Order By: Relevance
“…There was a strong negative correlation between initial loading ratio and PO4-P removal efficiency (r=-0.72, p=0.008). Our results for orthophosphate removal efficiency were in line with other studies which reported removal efficiencies of between 38 % and 95 % (Sarkhot et al, 2013;Zeng et al, 2013). We did not investigate the mechanisms involved in orthophosphate removal by biochar, but potential mechanisms suggested for orthophosphate removal from liquid solutions include phosphate adsorption to MgO on the biochar surface (Yao et al, 2011), precipitation reactions between phosphate and Ca + and Mg + ions (Wang et al, 2015c), anion exchange with surface hydroxyl groups (Sarkhot et al, 2013) and electrostatic interaction of phosphate anions with charged hydroxide surfaces (Chen et al, 2011).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…There was a strong negative correlation between initial loading ratio and PO4-P removal efficiency (r=-0.72, p=0.008). Our results for orthophosphate removal efficiency were in line with other studies which reported removal efficiencies of between 38 % and 95 % (Sarkhot et al, 2013;Zeng et al, 2013). We did not investigate the mechanisms involved in orthophosphate removal by biochar, but potential mechanisms suggested for orthophosphate removal from liquid solutions include phosphate adsorption to MgO on the biochar surface (Yao et al, 2011), precipitation reactions between phosphate and Ca + and Mg + ions (Wang et al, 2015c), anion exchange with surface hydroxyl groups (Sarkhot et al, 2013) and electrostatic interaction of phosphate anions with charged hydroxide surfaces (Chen et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…Effect of the initial loading ratio on nutrient and organic matter removal Several potential mechanisms for ammonium removal by biochar from liquid solutions have been proposed: cation exchange with cations such as Ca 2+ , Mg 2+ , K + , Na + in biochar (Hale et al, 2013;Sarkhot et al, 2013;Zeng et al, 2013;Cui et al, 2016), chemical reactions with (oxygen-containing) surface functional groups (Kizito et al, 2015;Wang et al, 2015aWang et al, , 2015cCui et al, 2016), surface areadependent physical diffusion and physical entrapment of NH4 + in biochar pores (Clough et al, 2013;Kizito et al, 2015), co-adsorption with soluble organic matter (Lehmann et al, 2002;Sarkhot et al, 2013) and struvite (MgNH4PO4.6H2O) precipitation on biochar (Cui et al, 2016). Lehmann et al (2002) attribute ammonium adsorption to the coadsorption with soluble organic matter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors concluded that BC from pine bark pyrolyzed at 650 °C adsorbed a higher quantity of phenols, coinciding with our study. These physical characteristics promote an effective adsorption of molecules because of the increased surface area and rougher texture of biochar, which improves the adsorption capacity of BC with organic molecules [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%